Validating a Brief Student Distress Measure For Schoolwide Wellness Surveillance. (June 2023) - Dowdy, Erin; Furlong, Michael J.; Nylund-Gibson, Karen; Arch, Dina; Hinton, Tameisha; Carter, Delwin
The original Social Emotional Distress Survey–Secondary (SEDS-S) assesses adolescents' past month's experiences of psychological distress. Given the continued need for and use of brief measures of student social-emotional distress, this study examined a five-item version (SEDS-S-Brief) to evaluate its use for surveillance of adolescents' wellness in schools. Three samples completed the SEDS-S-Brief. Sample 1 was a cross-sectional sample of 105, 771 students from 113 California secondary schools; responses were used to examine validity evidence based on internal structure. Sample 2 consisted of 10, 770 secondary students who also completed the Social Emotional Health Survey-Secondary-2020, Mental Health Continuum–Short Form, Multidimensional Student Life Satisfaction Scale, and selected Youth Risk Behavior Surveillance items (chronic sadness and suicidal ideation). Sample 2 responses examined validity evidence based on relations to other variables. Sample 3 consisted of 773 secondary students who completed the SEDS-S-Brief annually for 3 years, providing response stability coefficients. The SEDS-S-Brief was invariant across students based on sex, grade level, and Latinx status, supporting its use across diverse groups in schools. Additional analyses indicated moderate to strong convergent and discriminant validity characteristics and 1- and 2-year temporal stability. The findings advance the field toward comprehensive mental health surveillance practices to inform services for youth in schools.